Increasing student engagement and retention in e-learning environments Web 2.0 and blended learning technologies - Wankel, Charles; Blessinger, Patrick (Bingley, U.K. : Emerald, 2013)
Increasing Student Engagement and Retention in e-Learning Environments: Web 2.0 and Blended Learning Technologies examines new research on how online and blended learning technologies are being used in higher education to increase learner engagement in an era of increasing technological convergence and dependence. These enabling technologies are reshaping and reframing the practice of teaching and learning in higher education. Through case studies, surveys, and literature reviews, this volume will examine online and blended technologies are being used to improve academic literacies in students, to create engaging communities of practice, and how these technologies are being used to improve learner motivation and self-empowered learners. This volume will also discuss a framework for adopting and deploying these technologies.
Novel approaches in higher education : an introduction to Web 2.0 and blended learning technologies / Patrick Blessinger, Charles Wankel -- Leadership from ID (instructional design) for Web 2.0 adoption : appropriate use of emerging technologies in online courses / Marcia L. Ashbaugh -- Controlling engagement : the effects of learner control on engagement and satisfaction / Michael N. Karim, Tara S. Behrend -- Increasing learner engagement of learning technologies and science TPACK through representational challenges / Peter Hubber, Esther Loong -- From connectivity to connected learners : transactional distance and social presence / David Starr-Glass -- Promoting learner engagement and academic literacies through blended course design / Cathy Gunn -- Engaging learners as moderators in an online management course / Kamna Malik -- Engaging entrepreneurs with a blended problem-based learning degree programme / Patrick Lynch ... [et al.] -- Engaging distance and blended learners online / Andrew Doig, Steve Hogg -- A pedagogical framework for collaborative learning in a social blended e-learning context / Martina A. Doolan -- Developing technology and collaborative group work skills : supporting student and group success in online and blended courses / Julia L. Parra -- Balancing students' privacy concerns while increasing student engagement in e-learning environments / Lynne Siemens, Catherine Althaus, Charlotte Stange -- Problem-based learning in hybrid, blended, or online courses : instructional and change management implications for supporting learner engagement / Katerina Bohle Carbonell ... [et al.].
Includes indexes.
Keywords: Education -- Computers & Technology; Education -- Distance Education & Learning; Teachers' classroom resources & material; Educational: IT & computing, ICT; Computer-assisted instruction; Education -- Effect of technological innovations on